Registration of 'CI0947bmr' Sorghum. Issue 3 (25th July 2014) - Portillo, O. R.; Clara-Valencia, R.; Ramírez, J.; Estebez, R.; Hernández, M.; Morán, A.; Obando, R.; Gutiérrez, N.; Tinoco-Mora, R.; De Gracia, N.; Herrera, D.; Tedeschi, L.; et al.
Abstract : The sorghum [ Sorghum bicolor (L.) Moench] cultivar CI0947 bmr (Reg. No. CV‐137, PI 672153) was jointly developed and released by the Centro Nacional de Tecnología Agropecuaria y Forestal (CENTA) research program in El Salvador and the Texas A&M Agrilife Research sorghum breeding program in 2013. CI0947 bmr is a brown midrib ( bmr ), dual‐purpose sorghum selected for productivity in Central American environments. CI0947 bmr was developed from a pedigree breeding program, and it was derived from a BC1 F2 population of the pedigree B03292 bmr /Tortillero//Tortillero. All generation advancement and selection were completed in San Andres, El Salvador. To confirm performance of the line, CI0947 bmr was evaluated in replicated yield trials in 10 Central American environments ranging from Panama to Guatemala in 2010 and 2011. Compared with Sureno (a non‐ bmr dual‐purpose sorghum cultivar grown in the region), CI0947 bmr is similar in maturity, dry biomass yield, grain yield, and composition, with lower concentration of lignin and higher in vitro dry matter digestibility and total digestible nutrients. Given these characteristics, CI0947 bmr can be used for forage production (grazing and silage) or for grain production with the post‐harvest plant residue suitable as forage. In addition, producers can save seed for replanting. This cultivar is designed to provide small livestock producers and dairies in Central America with access to sorghum forage with improved forage quality without sacrificing dry matter yield, grain yield, or grain quality.